Routine MRI findings of the asymptomatic foot in diabetic patients with unilateral Charcot foot - Poll, Ludger W (BioMed Central, 2010)
BACKGROUND: Imaging studies of bones in patients with sensory deficits are scarce. AIM: To investigate bone MR images of the lower limb in diabetic patients with severe sensory polyneuropathy, and in control subjects without sensory deficits. METHODS: Routine T1 weighted and T2-fat-suppressed-STIR-sequences without contrast media were performed of the asymptomatic foot in 10 diabetic patients with polyneuropathy and unilateral inactive Charcot foot, and in 10 matched and 10 younger, non-obese unmatched control subjects. Simultaneously, a Gadolinium containing phantom was also assessed for reference. T1 weighted signal intensity (SI) was recorded at representative regions of interest at the peritendineal soft tissue, the tibia, the calcaneus, and at the phantom. Any abnormal skeletal morphology was also recorded. RESULTS: Mean SI at the soft tissue, the calcaneus, and the tibia, respectively, was 105%, 105% and 84% of that at the phantom in the matched and unmatched control subjects, compared to 102% (soft tissue), 112% (calcaneus) and 64% (tibia) in the patients; differences of tibia vs. calcaneus or soft tissue were highly significant (p < 0.005). SI at the tibia was lower in the patients than in control subjects (p < 0.05). Occult traumatic skeletal lesions were found in 8 of the 10 asymptomatic diabetic feet (none in the control feet). CONCLUSION: MR imaging did not reveal grossly abnormal bone marrow signalling in the limbs with severe sensory polyneuropathy, but occult sequelae of previous traumatic injuries.